Analisis Penerapan Akuntansi Lingkungan dalam Mengukur Dampak Sosial Perusahaan - Omaleng, Julince (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study aims to analyze the implementation of environmental accounting in measuring the social impacts caused by mining company activities. The research employs environmental accounting indicators such as environmental liabilities, environmental recognition, and environmental assets to evaluate the extent of corporate responsibility for both social and environmental impacts. A descriptive qualitative approach was applied, using data collection techniques such as remote interviews, document analysis, and online questionnaires via Google Forms. A total of 110 valid responses were collected for this study. Data were analyzed using Descriptive Statistical Analysis with SPSS version 25. The findings indicate that the company’s implementation of environmental accounting remains suboptimal and has not met the expectations of the surrounding community. Corporate social and environmental responsibility is considered insufficiently transparent. Moreover, the practice of environmental accounting does not yet reflect or accommodate the needs, rights, and cultural values of local communities. As a result, the community has not fully benefited from the company’s social and environmental programs. The originality of this research lies in integrating the social and cultural dimensions of indigenous communities into environmental accounting analysis, an aspect rarely highlighted in previous mining-related studies. Keywords: Environmental Accounting, Social Impact, Environmental Liabilities, Environmental Recognition, Environmental Assets.